The HYDRODYNAMICS AND MASS TRANSFER IN A VIBRATING PLATE EXTRACTION COLUMNS: HYDRODYNAMICS AND MASS TRANSFER IN A VIBRATING PLATE EXTRACTION COLUMNS - Sovilj, Milan (Journal on Processing and Energy in Agriculture, 2026)
ABSTRACT In this work experimental data available in the literature presenting the results of different studies on hydrodynamics and mass transfer in two-phase liquid-liquid (L-L) extraction columns with vibrating perforated plates (VPE) were considered. The data for different two-phase L-L systems were analyzed. The following hydrodynamic characteristics were observed: the mean drop diameter, dispersed-phase hold-up, relative velocity, and flooding velocity. The influence of operating parameters such as the agitation speed, superficial velocity of the continuous and dispersed phases, and the direction of mass transfer on the hydrodynamic characteristics of the VPE column was established. Empirical correlations for the prediction of hydrodynamic characteristics based on the data for operating parameters: column geometry, and physical properties of the fluids were presented and analyzed from the point of view of applicability. In addition, the mass transfer coefficients in VPE columns were presented and commented.